Integration of AI Chatbot in Digital Marketing Strategy: A Case Study on E-commerce Skincare - Alifah, Nur (Journal of Digital Marketing and Search Engine Optimization, 2025)
The development of digital technology is driving a major transformation in marketing strategies, one of which is through the integration of Artificial Intelligence (AI)-based chatbots in the e-commerce sector. This research is motivated by the need for skincare e-commerce to increase customer engagement, accelerate sales conversion, and build loyalty through a more personalized and efficient approach. This study aims to analyze the effect of AI chatbot integration in digital marketing strategies on customer engagement, sales conversion, and customer loyalty in the skincare e-commerce industry. The research method uses a descriptive qualitative approach with data collection techniques through in-depth interviews, observation, and documentation on several skincare e-commerce in Indonesia. Data were analyzed using the Miles and Huberman interactive analysis model, which includes data reduction, data presentation, and conclusion drawing. The results showed that the integration of an AI chatbot was able to increase the average duration of customer interactions, accelerate the buying process by increasing the conversion rate from 2.3% to 5.7%, and strengthen customer loyalty through data analytics-based personalization services. AI chatbots play an important role in optimizing the customer journey in a faster and more relevant way. The conclusion of this study confirms that the use of AI chatbots can be an effective strategy in strengthening the competitive position of skincare e-commerce in the digital era. The practical implications of this research encourage companies to develop chatbots based on customer behavior analytics and pay attention to customer data security aspects.